Undergraduate Students’ Self-Efficacy Strategies in Writing Academic Papers - Sumarsono, Anne Yustica Pramesti; Mbato, Concilianus Laos (Language Circle: Journal of Language and Literature, 2021)
This study explored the writing self-efficacy of English education undergraduates at Sanata Dharma University, Yogyakarta. Nowadays, many students still have not used self-efficacy in their studies. Consequently, they may encounter difficulties when working on tasks. As a result, the scores obtained are not the highest. Which may make them lack the motivation to learn. The purpose of this research was to determine the application of self-efficacy in writing works for the undergraduate course of English Education at Sanata Dharma University. The research question was: How can undergraduate students of the English Education Study Program manage self-efficacy and writing anxiety to complete the academic writing class? This research adopted qualitative methods making use of the Likert scale and interviews. The questionnaire was distributed to Sanata Dharma University’s undergraduates who had received English courses in reading literary works. The results show that undergraduates have a high sense of self-efficacy, can complete academic writing on time, and we are motivated by their internal and surrounding environments.